Analisis Kebutuhan Pengembangan Instrumen Literasi Lingkungan Untuk Mahasiswa Pendidikan Biologi FKIP Universitas Ahmad Dahlan - Yahya Hanafi; Nani Aprilia; Arief Abdillah Nurusman; Agung Purwanto; Nadiroh Nadiroh; Setia Budi (JURNAL EKSAKTA PENDIDIKAN (JEP), 2021)
The decline in environmental quality is a severe problem that occurs in various countries in the world. The decline in environmental quality can occur due to several factors, including habitat degradation (pollution), ecosystem damage, and global climate change. Instilling an attitude of caring for the environment in higher education can be done through Environmental Education materials integrated into several courses or stand as a separate subject. The ultimate goal of Environmental Education is to make students have environmental literacy (environmental literacy). This study aimed to analyze the need for the development of environmental literacy instruments and to develop prototypes of literacy instruments. This research is a type of survey research. The research carries out in May – September 2019 at the Biology Education Study Program, FKIP UAD. Data collection techniques using questionnaires and unstructured interviews with questionnaire data collection instruments. Descriptive data analysis technique. Environmental science courses provide information on current environmental issues that students urgently need. After taking environmental science courses, students feel that environmental literacy has increased, but the level of environmental literacy is not yet known. Students and lecturers feel the need to see the level of environmental literacy, so it is necessary to develop an instrument to measure environmental literacy. The literacy instrument that will develop refers to the NAAEE consisting of four components, namely Competence (identification, analysis, investigation, and solution of environmental problems; knowledge (ecological concepts, environmental concepts, and environmental components); disposition (ideas/ideas, concern), sensitivity. ). , solutions to environmental problems); behavior (commitment to care for the environment and concrete actions to care for the environment).